Development of NSAID‐loaded nano‐composite scaffolds for skin tissue engineering applications. Issue 8 (3rd July 2020) - Zehra, Mubashra; Mehmood, Azra; Yar, Muhammad; Shahzadi, Lubna; Riazuddin, Sheikh
Abstract: Scar free healing together with pain management is one of the major considerations in full thickness wound healing. Extensive wounds take longer to heal without any clinical intervention and, hence, need natural or artificial extracellular matrix support for quick skin regeneration. To address these issues, medicated 3D porous biomimetic scaffolds were developed with a unique combination of biopolymers, that is, chitosan, sodium alginate, and elastin, supplemented with a non‐steroidal anti‐inflammatory drug (NSAID). Scaffolds were physically characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), swelling ratio analysis, and degradation studies. Findings of the performed analyses proved that these skin substitutes suitable for skin tissue engineering applications attributable to their nano‐microporous structures (pore size in range of 0.085–256 μm) allowing cell infiltration and high‐water absorption capacity for management of wound exudates. Optimal dose of the loaded ibuprofen was estimated by evaluating effect of variable concentrations of ibuprofen (control, ILM‐10, ILM‐15, and ILM‐20) on adipose tissue‐derived mesenchymal stem cells (ASCs) proliferation rate. Out of all experimental groups, ILM‐20 constructs were found to accelerate the proliferation rate of seeded ASCs confirming their non‐cytotoxic characteristics as well potential to be used for translational scaffold‐based therapies.